Money a rich history - Anderson, Jon R. 1963-; Wickstrom, Thor. (New York Grosset & Dunlap, 2003)
Briefly relates the origins and history of money, how coins and paper money are made and other money-related facts, presented in the form of a child's school report.
Keywords: Money -- History; Money